Event-Based Clustering Architecture for Power Efficiency in Wireless Sensor Networks - Kai-Ting Yang; Wei Kuang Lai; Shu-Min Li; Yuh-Chung Lin (International Journal of Distributed Sensor Networks, 2014)
In order to set up WSN in various rigorous environments, the size and power constraints are stricter due to the high demands for convenience and reliability. Therefore, power efficiency is very important for a WSN. For this, a novel architecture is presented in this paper. The proposed architecture categorizes sensors into different clusters by events. In each cluster, a minimum spanning tree is constructed for intracluster routing. The hierarchical architecture is useful in reducing the power consumption. In each intracluster routing tree, only leaf nodes are responsible for periodical detection. Data transmissions only occur when abnormal events are detected. An abnormality will be reported to the data center only if the majority of cluster members sense the same event. By reducing unnecessary data transmissions and shortening transmission distances, the proposed mechanism significantly reduces the power consumption and prolongs the network lifetime without influencing the accuracy of event response. The simulations show that the proposed architecture has about an 18-fold improvement rate in the device lifetime and avoids the false positive caused by the erroneous alarm of a single sensor. The proposed architecture is feasible, practical, and highly applicable to many applications.